Total health expenditure and outcomes - Lago, Fernando Pablo (2013)
The aim of this paper is to analyze the relationship between total health expenditure, national income and population health status for a large sample of countries. We performed a descriptive, quantitative, ecological analysis based on data from 192 countries provided by the World Health Organization (WHO) for the years 2000 and 2009. The indicators used to measure health status are the life expectancy at birth and the infant mortality rate. While this study does not allow conclusions regarding the existence of causality, the statistical analysis performed suggest that there is a positive and stable relationship between health results, per capita health expenditure and per capita national income.